Dari Ladang ke Pasar: Mengurai Jejak Ekonomi Pertanian di Jember - Erlin Kurniati; Ayu Sukma Wardhani (Yayasan Literasi Sains Indonesia, 2025)
Jember Regency is one of the agricultural regions that plays a significant role in the economy of East Java. With agriculture being the dominant sector in the livelihood structure of its population, agriculture in Jember not only serves as a source of income but also determines the social and economic dynamics of the region. This article delves deeply into how agricultural activities, from upstream to downstream, from production processes in the fields to distribution to the market, shape the regional economic structure. The study findings show that although Jember has a comparative advantage in commodities such as coffee, cocoa, tobacco, rice, and horticulture, the added value received by farmers remains relatively low. Contributing factors include dependence on middlemen, limited access to post-harvest technology, limited marketing networks, and a lack of innovation in product processing, resulting in a weak bargaining position for farmers in the market. In addition, supporting infrastructure such as agricultural roads, irrigation systems, storage facilities, and price information systems are still inadequate. On the other hand, there are significant untapped potentials, including opportunities for agricultural digitization, strengthening farmers' economic institutions such as cooperatives and local government-owned enterprises (BUMD), and collaboration between local governments, universities, and the private sector.